One‐Step Construction of Ordered Sulfur‐Terminated Tantalum Carbide MXene for Efficient Overall Water Splitting. Issue 3 (29th December 2021) - Wu, Tong; Pang, Xin; Zhao, Siwei; Xu, Shumao; Liu, Zhanqiang; Li, Yongsheng; Huang, Fuqiang
Abstract : Hydrogen production from electrolyzed water plays an important role in clean energy system, but the current reported non‐noble metal catalysts still need to be paired with commercial Pt/C or RuO2 for overall water splitting. It is still a great challenge to develop high activity and stability bifunctional catalysts for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in the same medium. To date, the emerging 2D MXenes have been extensively studied in the field of electrocatalysis because of their interesting surface physicochemical characteristics. However, the preparation process is very complex and difficult. Their intrinsic electrocatalytic properties are not good enough due to the disordered terminal groups (‐OH/‐F/‐Cl). Herein, the traditional preparation procedure is optimized, and the 2D layered compound Ta2 CS2 is directly synthesized by a one‐step method. Unlike the typical MXenes with disorderly terminated groups, Ta2 CS2 is terminated orderly with S atoms, and it shows excellent conductivity and electrochemical properties. Based on the great performance for OER and HER, the exfoliated Ta2 CS2 (Ta2 CS2 ‐E) is found to be an outstanding bifunctional catalyst of MXenes‐based materials for overall water splitting. Abstract : A novel bifunctional electrocatalyst of metallic Ta2 CS2 is designed and exfoliated for alkaline overall water splitting. The constructed water electrolyzer requires only a low cell voltage of 1.51 V to reach 10 mA cm −2 with ≈100% current density retention over 100 h, superior to the performance of commercial RuO2 ║ Pt/C (1.64 V@10 mA cm −2 ) and most reported MXenes‐based catalysts.